Assessment of Affect Lability: Psychometric Properties of the ALS-18 - Contardi, Anna; Imperatori, Claudio; Amati, Italia; Balsamo, Michela; Innamorati, Marco (Frontiers in Psychology, 2018)
Affect lability, an important aspect of emotion dysregulation, characterizes several psychiatric conditions. The short Affective Lability Scales (ALS-18) measures three aspects of changeability between euthymia and affect states (Anxiety/Depression, AD; Depression/Elation, DE; and Anger, Ang). The aim of our study was to investigate the psychometric characteristics of an Italian version of the ALS-18 in a sample of adults recruited from the general population. The sample was composed of 494 adults (343 women and 151 men) aged 18 and higher (mean age = 31.73 years, SD = 12.6). All participants were administered a checklist assessing socio-demographic variables, the ALS-18 and measures of depression and difficulties in emotion regulation. Confirmatory factor analyses indicated adequate fit of the three-factor model (RMSEA = 0.061, 95% CI = 0.054/0.069; CFI = 0.99; SRMR = 0.055), and the presence of a higher-order general factor. Internal consistency was satisfactory for all the lower-order dimensions and the general factor (ordinal α > 0.70). The ALS-18 was significantly associated with concurrent measures of depression and difficulties in emotion regulation. These findings indicate that the ALS-18 is a valid and reliable instrument for measuring affect lability, although discriminant validity of subdimensions scores could be problematic.